Perception of Polish Consumers Regarding HACCP / ISO 22000 Quality Systems - Magdalena NIEWCZAS-DOBROWOLSKA (Communications of International Proceedings, 2021)
Food label is one of the sources of food information for consumers, it is the easiest way to collect information about food. In the food market the information asymetry can be identified what means that producers have more information about food products than consumers have. Consumers in many cases cannot i.e. check the product quality by their senses because usually products are packaged. To reduce this asymetry producers place various information about food product on their labels, i.e. certificates. Certificates of quality and safety standards such as HACCP or ISO 22000 may reduce this information asymetry. Information about these systems on the food labels may be a sign of higher product quality to consumers.  In this study the results of the survey made in 2020 in Poland among 2000 consumers are shown. According to results it can be said that many consumers do not know what HACCP/ISO 22000 is, so their role to attract consumers is rather low. Consumers who are more involved in purchase decisions more often perceive these standards as a sign of a safe product or a product of higher quality.
Keywords: food quality; perception; food quality standards